Lingwistyka dyskursu i lingwistyka mediów – perspektywa germanistyczna - Marcelina Kałasznik (Linguistische Treffen in Wrocław)
Research topics such as discourse or discursivity, media or mediality and multimodality are at the centre of studies by both Polish and German-speaking linguists. If one observes the research in this area conducted in Poland and in German-speaking countries, similarities and differences become apparent. Based on the assumption that representatives of the Polish and German research cultures partly represent different approaches, initiatives that enable a dialogue between these two research traditions are extremely important. The publication to be presented in the article „Dyskurs, media, multimodalność. Przyczynek do dialogu germanistyczno-polonistycznego“, which was published in 2022 by Waldemar Czachur, Anna Hanus and Dorota Miller, aims to provide Polish readers with an insight into the research findings of the German studies community. The monograph consists of two parts. The first part is devoted to discourse linguistics and contains translations of five articles by German researchers. The second part of the publication which focusses on media linguistics, includes translations of four articles by German researchers into Polish. The two parts also contain interviews with German and Polish linguists and media scholars, in which the problems of discourse, media texts, multimodality and media linguistics are discussed.